THE EFFECT OF PROFITABILITY, ASSETS STRUCTURE, AND LIQUIDITY ON CAPITAL STRUCTURE FOOD AND BEVERAGE COMPANY WHICH IS REGISTERED ON BEI 2019-2022 - Isma Putri Agustina; Rico Nur Ilham; Muttaqien; Chairil Akhyar (Universitas Efarina, 2023)
This research aims to analyze the influence of profitability, asset structure and liquidity on the capital structure of Food and Beverage Companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The population in this study were 43 Food and Beverage Companies registered on the IDX 2019-2022. The samples selected based on purposive sampling technique were 24 Food and Beverage Companies and had 96 observations. This research uses secondary data. The estimated model used is panel data regression analysis with the Fixed Effect Model. The research result show that Profitability has a negative and insignificant effect on Capital Structure, Asset Structure has a negative and significant effect on Capital Structure, Liquidity has a negative and insignificant effect on Capital Structure.